Adaptive control for a one-link robot arm actuated by pneumatic muscles - Karnjanaparichat T. (2014)
Presently artificial pneumatic muscles are used in various applications due to their simple construction, lightweight and high force to weight ratio. However, controls of various mechanical systems actuated by pneumatic muscles are facing various problems. The parameters of the muscles are nonlinear and time-varying due to temperature change and the deterioration of the pneumatic muscle materials when the muscles are used for an extended period of time. Therefore, adaptive control is suitable to solve control problems for the pneumatic muscles since it can be designed to be independent of all system parameters and be able to adapt to certain changes of the system parameters. In this paper, we study the problem of adaptive output tracking for a one-link robot arm actuated by two opposing pneumatic muscle groups. The two muscle groups are arranged to simulate the physiological model of the bicep-tricep system. An adaptive controller is designed under the condition that all physical parameters, such as the pneumatic muscle coefficients, length of the arm, mass, moment of inertia and etc., are unknown. Under this condition, we can prove that closed-loop trajectory of the joint angle can follow any C1 signal and the angle error will be within a prescribed error in a finite time. Simulations are presented to demonstrate the robustness of our adaptive controller under serve changes of the system parameters.